Neuroprotective Effects of Activated Protein C Involve the PARP/AIF Pathway against Oxygen-Glucose Deprivation in SH-SY5Y Cells - Sriwastva, Mukesh Kumar (Brain Sci, 2020)
Protein C, a member of the zymogen family of serine proteases in plasma, is one of the several vitamin K dependent glycoproteins known to induce anti-apoptotic activity. However, the target molecule involved in the mechanism needs to be investigated. We sought to investigate the pathways involved in the anti-apoptotic role of activated protein C (APC) on oxygen-glucose deprivation (OGD) induced ischemic conditions in in-vitro SH-SY5Y cells. SH-SY5Y cells were exposed to OGD in an airtight chamber containing 95% N(2) and 5% CO(2) and media deprived of glucose for 4 h following 24 h of reoxygenation. The cell toxicity, viability, expression of receptors such as endothelial cell protein C receptor (EPCR), protease-activated receptor (PAR)1, PAR3, and apoptosis-related proteins B-cell lymphoma 2 (BCL-2), BCL-2-like protein 4 (Bax), Poly [ADP-ribose] polymerase-1 (PARP-1) were assessed. Administration of APC decreased the cellular injury when compared to the OGD exposed group in a dose-dependent manner and displayed increased expression of PAR-1, PAR-3, and EPCR. The APC treatment leads to a reduction in PARP-1 expression and cleavage and apoptosis-inducing factor (AIF) expression. The reduction of caspase-3 activity and PARP-1 and AIF expression following APC administration results in restoring mitochondrial function with decreased cellular injury and apoptosis. Our results suggested that APC has potent protective effects against in-vitro ischemia in SH-SY5Y cells by modulating mitochondrial function.